High-Dose Asian Ginseng (Panax Ginseng) for Cancer-Related Fatigue: A Preliminary Report. (September 2015) - Yennurajalingam, Sriram; Reddy, Akhila; Tannir, Nizar M.; Chisholm, Gary B.; Lee, Richard Tsong; Lopez, Gabriel; Escalante, Carmen P.; Manzullo, Ellen F.; Frisbee Hume, Susan; Williams, Janet L.; Cohen, Lorenzo; Bruera, Eduardo
Introduction and Objective . Cancer-related fatigue (CRF) is the most common and severe symptom in patients with cancer. The number and efficacy of available treatments for CRF are limited. The objective of this preliminary study was to assess the safety of high-dose Panax ginseng (PG) for CRF. Methods . In this prospective, open-label study, 30 patients with CRF (≥4/10) received high-dose PG at 800 mg orally daily for 29 days. Frequency and type of side effects were determined by the National Cancer Institute's Common Terminology Criteria for Adverse Events, version 4.0. Scores on the Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-F) scale, Edmonton Symptom Assessment System (ESAS), and Hospital Anxiety and Depression Scale (HADS) were assessed at baseline, day 15, and day 29. Global Symptom Evaluation (GSE) was assessed at day 29. Results . Of the 30 patients enrolled, 24 (80%) were evaluable. The median age was 58 years; 50% were females, and 84% were white. No severe (≥grade 3) adverse events related to the study drug were reported. Of the 24 evaluable patients, 21 (87%) had an improved (by ≥3 points) FACIT-F score by day 15. The mean ESAS score (standard deviation) for well-being improved from 4.67 (2.04) to 3.50 (2.34) ( P = .01374), and mean score for appetite improved from 4.29 (2.79) to 2.96 (2.46) ( P = .0097). GSE score of PG for fatigue was ≥3 in 15/24 patients (63%) with median improvement of 5. Conclusion . PG is safe and improves CRF fatigue as well as overall quality of life, appetite, and sleep at night. Randomized controlled trials of PG for CRF are justified.